Political dimension to child and adolescent with special health needs care: a reflection - Andressa da Silveira; Eliane Tatsch Neves (Universidade Federal de Santa Maria, 2017)
Objective: to reflect on the political dimension in health care of children and adolescents with special health needs. Method: reflective analysis of current health policies, which are related to the health of children and adolescents, considering the demands made by these children. Results: we present some milestones in the social and public policies of child and adolescent health, including the inclusion of the rights that ensure universal access to health care. Among the social policies, there is the Organic Law of Social Assistance. Conclusion: Despite the fact that public health policies ensure the rights of children and adolescents, they do not meet the specificities of the demands of this population that need to be highlight. It is necessary to recognize this clientele in epidemiological rates in the national scenario. The equity perspective is essential for the unequal who, often, do not find spaces in health services